Association between glycaemic outcome and BMI in Danish children with type 1 diabetes in 2000–2018: a nationwide population‐based study. Issue 3 (4th November 2020) - Ibfelt, E. H.; Vistisen, D.; Falberg Rønn, P.; Pørksen, S.; Madsen, M.; Kremke, B.; Svensson, J.
Abstract: Aim: To describe the development of HbA1c and BMI over time in Danish children with type 1 diabetes; and to investigate the association between HbA1c and BMI including influence of age, gender, diabetes duration, severe hypoglycaemia and treatment method. Methods: We used the nationwide Danish Registry of Childhood and Adolescent Diabetes, DanDiabKids, including annual registrations of all children with diabetes treated at Danish hospitals. With linear mixed‐effects models and splines we analyzed the HbA1c and BMI development over time as well as the association between HbA1c and BMI including effects of gender, age, disease duration, hypoglycaemia and treatment method. BMI z‐scores were calculated for these analyses. Results: For the period from 2000 to 2018, 6097 children with type 1 diabetes were identified from the DanDiabKids database. The median (interquartile range) HbA1c level was 65 (57–74) mmol/mol (8.1%) and the median BMI z‐score was 0.85 in girls and 0.67 in boys. A non‐linear association was found between HbA1c and BMI z‐score, with the highest BMI z‐score observed for HbA1c values in the range of approximately 60–70 mmol/mol (7.6–6.8%). The association was modified by gender, age and diabetes duration. Severe hypoglycaemia and insulin pump treatment had a small positive impact on BMI z‐score. Conclusion: The association between HbA1c and BMI z‐score was non‐linear, with the highest BMI z‐score being observed for intermediate HbA1c levels; however, specific patterns depended on gender, age and diabetes duration.